Numerical and Experimental Study of the Hybrid Savonius - Darrieus 3 Blade with NACA 4418 Airfoil - Kusumadewi, Tri Vicca; Mikael, William; Setiyawan, Atok; Pertiwi, Fungky Dian (Journal of Applied Sciences, Management and Engineering Technology, 2024)
This study presents the design, simulation, and experimental validation of a novel hybrid Savonius-Darrieus vertical axis wind turbine (VAWT) utilizing NACA 4418 airfoil blades. The aim is to investigate the performance characteristics of the turbine under various wind conditions. The turbine design integrates Savonius and Darrieus configurations to harness wind energy efficiently. Computational Fluid Dynamics (CFD) simulations are conducted using software [mention the software] to analyze the aerodynamic behavior and predict turbine performance. The NACA 4418 airfoil profile is employed due to its favorable lift-to-drag ratio and widely used characteristics. Simulation’s results demonstrate that the optimal torque is the Darrieus blade 3 by 1.06 Nm at an azimuth angle of 75°, followed by Savonius 1 by 0.96 Nm at an azimuth angle of 285° on wind speed of 5 m/s. The turbine's power output, coefficient of power (CP), and coefficient of moment (Cm) across a range of wind speeds (3 to 5 m/s) on simulation and experimental are compared. The power output of the experimental by 1.54 watts and 13.14 watts for the simulation this also indicated that CP in the simulation was 8 times higher than the experimental. The maximum torque of 0.11 Nm in the experimental, compared to 0.36 Nm for simulation occurs the CM result will be similar. The design, configuration, and environment play a crucial role in determining the performance characteristics.